2010
DOI: 10.1179/037178410x12644261583025
|View full text |Cite
|
Sign up to set email alerts
|

Passing bays in an underground mine

Abstract: Some mining companies are investigating the use of road trains to increase productivity in underground mines. Road trains require dedicated passing bays in declines. The spacing of these passing bays can have a significant impact on haulage productivity. This technical note describes the use of simulation to find the optimal spacing. If the distance between passing bays is sufficiently small then descending trains can be interleaved with ascending trains, which increases productivity. If the spacing is too sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…We observed in our previous paper (Anjomshoa et al, 2010) that the best locations of a fixed number of passing bays are those that are precisely spaced to allow interleaving of vehicles without delays at bays, and we simulated the vehicle movements in a proposed underground mine to confirm this observation. Simulation has been widely used to study and improve operations in the mining industry.…”
Section: Introductionsupporting
confidence: 71%
See 4 more Smart Citations
“…We observed in our previous paper (Anjomshoa et al, 2010) that the best locations of a fixed number of passing bays are those that are precisely spaced to allow interleaving of vehicles without delays at bays, and we simulated the vehicle movements in a proposed underground mine to confirm this observation. Simulation has been widely used to study and improve operations in the mining industry.…”
Section: Introductionsupporting
confidence: 71%
“…We developed an algorithm that ensures that descending vehicles can be refuged in bays before encountering any ascending vehicles. Anjomshoa (2011) demonstrated that this deadlock avoidance method is less restrictive than the one implemented by Sturgul et al (1996), in which deadlock is avoided by allowing only ascending vehicles to follow on a segment.…”
Section: Problem Formulationmentioning
confidence: 92%
See 3 more Smart Citations